HUBUNGAN DUKUNGAN SOSIAL DAN KONSEP DIRI DENGAN STRATEGI COPING AKIBAT LOSE STREAK GAME MOBILE LEGENDS PADA DEWASA AWAL - Hernani Mariati; Agus Salim (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The increasing psychological pressure in the form of stress and frustration in early adulthood due to the inability to manage emotions after experiencing consecutive losses in digital games is the background of this research. These operational problems trigger the emergence of maladaptive behavioral responses that disrupt the mental stability of daily cyber players. The main focus of this scientific study is to dissect the relationship between social support and self-concept with coping strategies due to losing streaks in the Mobile Legends game in early adulthood. The steps of this correlational quantitative approach were operated through purposive sampling of 170 active respondents aged 18 to 40 years. Data collection used a standardized Likert scale questionnaire, which was then statistically analyzed using the Pearson correlation test. Quantitative data empirically revealed a significant positive correlation between social support (r = 0.538; p = 0.000) with a contribution of 16.5 percent, and self-concept (r = 0.552; p = 0.000) which contributed 34.1 percent. Simultaneously, the accumulated contribution of both independent variables reached a total of 50.6 percent. The main conclusion confirms that the effectiveness of managing game mechanics' stress is largely determined by the resilience of positive self-concept as an internal factor, reinforced by the supply of external social resources. Psychology practitioners are recommended to draft a consistent guidance module for the affective regulation of digital activities. ABSTRAK Meningkatnya tekanan psikologis berupa stres dan frustrasi pada usia dewasa awal akibat ketidakmampuan mengelola emosi pasca mengalami kekalahan beruntun dalam permainan digital melatarbelakangi penelitian ini. Masalah operasional tersebut memicu timbulnya respons perilaku maladaptif yang mengganggu stabilitas mental para pemain siber harian. Fokus utama kajian ilmiah ini adalah membedah hubungan antara dukungan sosial dan konsep diri dengan strategi coping akibat lose streak game Mobile Legends pada dewasa awal. Langkah-langkah pendekatan kuantitatif korelasional ini dioperasikan melalui penarikan sampel secara purposive sampling terhadap 170 responden aktif berusia 18 hingga 40 tahun. Pengumpulan data menggunakan kuesioner skala Likert terstandardisasi, yang selanjutnya dianalisis statistik lewat uji korelasi Pearson. Data kuantitatif secara empiris menyingkap korelasi positif signifikan pada dukungan sosial (r = 0,538; p = 0,000) dengan kontribusi 16,5 persen, serta konsep diri (r = 0,552; p = 0,000) yang menyumbang 34,1 persen. Secara simultan, akumulasi kontribusi kedua variabel independen mencapai total 50,6 persen. Simpulan utama menegaskan bahwa efisiensi pengelolaan stres mekanik game sangat didominasi oleh ketangguhan konsep diri positif sebagai faktor internal, yang diperkuat pasokan sumber daya sosial eksternal. Praktisi psikologi direkomendasikan menyusun draf modul bimbingan regulasi afektif aktivitas digital secara konsisten.